Removal of Methylene Blue from Aqueous Solution by Using Electrical Arc Furnace (EAF) Slag - Suhanna Natalya Mohd Suhaimy; Luqman Chuah Abdullah (Universitas Gadjah Mada, 2020)
In recent years, environmental protection has gained a major concern. In line with the rapid growth of various industries, high amount of effluent has been generated and discharged to the environment. One of the concerns is the presence of synthetic dye in the wastewater stream, as it may endanger human and aquatic life. In this experiment, the Electrical Arc Furnace (EAF) slag has been used as an adsorbent to remove methylene blue from the aqueous solution. Batch experiments have been conducted, and the effects of initial dye concentration, pH, adsorbent dosage and temperature were studied respectively. Chemical treatment has been performed to modify the adsorbent. The results reveal that treated EAF Slag has higher efficiency in removing methylene blue compared to raw EAF slag. More pores have been exposed, and impurities on the adsorbent’s surface have been removed, to enhance better removal efficiency. The maximum adsorption capacity for treated EAF is 14.2029 mg/g and for raw EAF Slag is 9.615 mg/g. The maximum removal percentage for treated EAF Slag is 71.01%, whereas raw EAF shows 37.19% removal at pH 10. Both raw EAF Slag and treated EAF slag fits the data for the Langmuir isotherm model which obeys the monolayer adsorption process.